Corruption Prevention of Village Funds to Realize Anti-Corruption Village - Judy Marria Saimima,; Juanrico A.S. Titahelu,; Patrick Corputty,; Muammar, (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2023)
Abstract This paper aims to describe and analyze how the form of corruption prevention of village funds can ideally be carried out to realize an anti-corruption village. This paper uses a normative type of research. The approach used in this paper is a conceptual approach (conceptual approach) and an analytical approach (analytical approach). The discussion in the paper presents that so far the eradication of corruption has focused more on the downstream region by relying on criminal legal means. the eradication of corruption should ideally be pursued optimally in the most upstream areas, namely prevention areas. This includes efforts to prevent corruption of village funds, which have often become "soft food" for irresponsible village government elements and village officials. For this reason, efforts that should be done include. First, seek community participation and active role in the discussion, management, and use of village funds; second, strengthening governance to prevent corrupt practices; third, strengthening supervision, especially regarding village governance; fourth, strengthening the quality of public services to gain full trust from the public and provide feedback instruments to determine public satisfaction with the performance performed; Fifth, strive for the empowerment of local wisdom that applies in the village, such as the role of customary law or local culture and encourage the involvement of various elements such as religious leaders, traditional leaders, community leaders, youth communities. Keywords: Corruption Prevention; Village Fund; Anti-corruption